2017
DOI: 10.5797/jnet.oa.2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CT High-density Area after Endovascular Treatment for Acute Ischemic Stroke

Abstract: Objective: To evaluate the relationship between the incidence of the CT high-density area that appears immediately after endovascular treatment for acute ischemic stroke with postprocedural hemorrhagic transformation and its significance in the clinical outcome.Methods: Ten patients with ischemic stroke of the anterior circulation encountered between May 2014 and December 2015 in whom recanalization could be achieved within 8 hours after the onset were retrospectively analyzed. In addition, 695 patients presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…9,12 Clinical outcomes of these hyperdensities on CT have been investigated previously; however, their relationship with hemorrhagic transformation after treatment and their prognosis value are not entirely understood. 8,12,21,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12 Clinical outcomes of these hyperdensities on CT have been investigated previously; however, their relationship with hemorrhagic transformation after treatment and their prognosis value are not entirely understood. 8,12,21,22…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic difficulties occasionally appear with the presence of high-density areas on follow-up computed tomography (CT) performed early after treatment. 811 These areas of hyperdensity on post-procedural CT have been described as post-intervention cerebral hyperdensities (PCHDs) and are common occurrences with an incidence of between 31.2 and 60.0%. 12–15 It may be secondary to contrast staining, hemorrhagic transformation or both.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown a significant difference in symptomatic hemorrhage between the cortical contrast accumulation group and the non-cortical group (39.4% vs. 4.3%, P=0.003), suggesting that widespread contrast accumulation could be related to extensive reperfusion injury (27,28). If covering about 20% or more of the hemisphere, the extent of contrast staining has a predictive value for brain edema or symptomatic hemorrhage in some studies (15,17,23). Variations may exist depending on the modality of endovascular treatment (whether a stent retriever is used or not), recanalization rate, occlusion site, the quality or timing of post-procedural CT scans, amount of contrast agents, and the average time for fluoroscopy, all of which can influence the pattern or the amount of contrast staining.…”
Section: Intraparenchymal Hyperattenuation After Mechanical Thrombectomymentioning
confidence: 98%
“…Takei et al (15) have suggested that those with MT show a higher incidence of hyperdensity lesions due to higher recanalization rates and mechanical injury of intracranial vessels with the stent retriever. Typically, such contrast enhancement will clear within the first 19-24 hours after the procedure without hematoma (4,16).…”
Section: Intraparenchymal Hyperattenuation After Mechanical Thrombectomymentioning
confidence: 99%
See 1 more Smart Citation